2020
DOI: 10.1155/2020/5629090
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning for the Preliminary Diagnosis of Dementia

Abstract: Objective. The reliable diagnosis remains a challenging issue in the early stages of dementia. We aimed to develop and validate a new method based on machine learning to help the preliminary diagnosis of normal, mild cognitive impairment (MCI), very mild dementia (VMD), and dementia using an informant-based questionnaire. Methods. We enrolled 5,272 individuals who filled out a 37-item questionnaire. In order to select the most important features, three different techniques of feature selection were tested. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 20 publications
(25 reference statements)
0
29
0
Order By: Relevance
“…Zhu et al . analyzed a Taiwan cohort and ranked the relative importance of neuropsychological tests using Information Gain, Random Forest, and the Relief algorithm [18]. They classified normal, MCI, VMD, and dementia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhu et al . analyzed a Taiwan cohort and ranked the relative importance of neuropsychological tests using Information Gain, Random Forest, and the Relief algorithm [18]. They classified normal, MCI, VMD, and dementia.…”
Section: Discussionmentioning
confidence: 99%
“…A large array of neurocognitive tests are currently used to detect cognitive impairment and classify amongst normal controls (CN), EMCI, LMCI and AD [7][8]. Many studies have identified a few top classifiers using logistic regression and machine learning methods [9][10][11][12][13][14][15][16][17][18]. Some studies have also used MRI and genetic data in conjunction with neurocognitive measures for classification [19][20].…”
Section: Introductionmentioning
confidence: 99%
“…This study is a retrospective analysis of the dementia registry database from the Show Chwan Healthcare System, currently applied in three centers in Taiwan (two in central Taiwan and one in southern Taiwan). In the database, the detailed clinical history of each participant was recorded using a structured questionnaire called the History-Based Artificial Intelligent Clinical Dementia Diagnostic System (HAICDDS), which has been well-validated (Lin et al, 2018 ; Chiu et al, 2019a , b , 2020 ; Tsai and Chiu, 2019 ; Chang et al, 2020 ; Wang et al, 2020 ; Zhu et al, 2020a , b ; Huang et al, 2021 ). In addition, CDR was used for staging dementia, and the daily function was assessed using the Instrumental Activities of Daily Living (IADL) Scale (Lawton and Brody, 1969 ) and Barthel Index (BI) (Mahoney and Barthel, 1965 ).…”
Section: Methodsmentioning
confidence: 99%
“…In our recent experience and studies using artificial intelligence (AI) for the diagnosis of cognitive impairment (CI) and dementia, the CDR and CDR-SB have become perfect references for machine learning in our newly designed questionnaires (Chiu et al, 2019a ; Chang et al, 2020 ; Zhu et al, 2020a , b ). Therefore, we highly recommend CDR as a further AI study.…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning and deep learning are commonly used in other fields. Such as in [29], machine learning algorithms are used for the preliminary diagnosis of Dementia. In [30], target recognition is made in SAR images based on multiresolution representations with 2D canonical correlation analysis.…”
mentioning
confidence: 99%